Evolution not revolution – what might the future hold for front‐of‐pack nutrition labelling in the UK?: A British Nutrition Foundation roundtable. Issue 3 (15th August 2021) - Gibson‐Moore, Helena; Spiro, Ayela
Abstract: Obesity and diet‐related chronic diseases remain a serious public health concern across the globe. As part of an integrated package of policies to tackle obesity, many countries use front‐of‐pack nutrition labelling (FOPNL), which can provide at‐a‐glance information to help consumers make healthier food choices. The UK government has recently run a consultation (July 2020–October 2020) on FOPNL to gather views and evidence on the current 'multiple traffic lights' (MTL) label scheme, and to compare other FOPNL schemes (such as the Chilean Warning and Nutri‐Score labels) in respect of their impact on consumer and industry behaviour. To identify and explore the strengths and limitations of different FOPNL systems, the British Nutrition Foundation hosted a virtual roundtable event with a wide range of stakeholders in October 2020. The ensuing discussions considered the effectiveness of FOPNL in guiding food purchases and healthier eating choices and in driving product reformulation; as well as the potential advantages, disadvantages, opportunities and challenges of different systems including MTL and Nutri‐Score. This report describes some of the key points emerging from the discussions.